How the body of Lazarus helps to solve a Pauline problem - Strawbridge, J (Cambridge University Press, 2017)
While the locus classicus for early Christian arguments concerning resurrection of the flesh is Paul’s first Corinthian letter, the statement in 15.50 that “flesh and blood cannot inherit the kingdom of God” complicates early Christian understandings of resurrection and its form. Such explicit denial of fleshly inheritance and resurrection within Paul’s writings leads to widely conflicting interpretations of this Corinthian passage. Consequently, early Christian writers such as Irenaeus, Tertullian, and Augustine engaged other New Testament texts such as John 11 in order to subvert the claim of 1 Cor 15.50 and develop their argument for fleshly resurrection.